2022
DOI: 10.3389/fphar.2022.794938
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Mechanism of Bushen Huoxue Decotion on Decidualization by Intervening Autophagy via AMPK/mTOR/ULK1: A Novel Discovery for URSA Treatment

Abstract: Impaired decidualization was recognized as one of the crucial pathomechanisms accounting for unexplained recurrent spontaneous abortion (URSA). Currently, the exact molecular mechanism and targeted clinical decision are still in exploration. Bushen Huoxue decoction (BSHXD) has previously been proved effective in treating URSA, but its mechanism remains to be elucidated. This study aimed to explore the regulation mechanism of BSHXD in decidualization from its intervention in autophagy so as to rationalize its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…As for the validation of signature genes decidua tissues were fixed with 4% paraformaldehyde and embedded in paraffin for immunofluorescence analysis, which was conducted following previously described methods ( 29 ). In this study, Vimentin representative decidual stromal cell and CX3CR1 representative macrophage.…”
Section: Methodsmentioning
confidence: 99%
“…As for the validation of signature genes decidua tissues were fixed with 4% paraformaldehyde and embedded in paraffin for immunofluorescence analysis, which was conducted following previously described methods ( 29 ). In this study, Vimentin representative decidual stromal cell and CX3CR1 representative macrophage.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was used to detect the expression levels of LC3II/LC3I and p62, the two of which can be used to evaluate the status of autophagy flux [34]. The results showed that the LC3II/LC3I ratio in the DHEA group decreased significantly, while p62 increased (Figure 5), indicating the decreased level of autophagy in the DHEA uterus.…”
Section: Steroidogenesismentioning
confidence: 99%
“…Autophagy is known to drive essential homeostatic mechanisms in uterus physiology and has been involved in uterus hyperplasia [33]. To quantify the level of autophagy, Western blotting was used to detect the expression levels of LC3II/LC3I and p62, the two of which can be used to evaluate the status of autophagy flux [34]. The results showed that the LC3II/LC3I ratio in the DHEA group decreased significantly, while p62 increased (Figure 5), indicating the decreased level of autophagy in the DHEA uterus.…”
Section: Autophagic Fluxmentioning
confidence: 99%